Aberrant DNA methylation of cancer-associated genes in gastric cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC-EURGAST). - Balassiano, K; Lima, S; Jenab, M; Overvad, K; Tjonneland, A; Boutron-Ruault, M; Clavel-Chapelon, F; Canzian, F; Kaaks, R; Boeing, H; Meidtner, K; Trichopoulou, A; et al. (2011)
Epigenetic events have emerged as key mechanisms in the regulation of critical biological processes and in the development of a wide variety of human malignancies, including gastric cancer (GC), however precise gene targets of aberrant DNA methylation in GC remain largely unknown. Here, we have combined pyrosequencing-based quantitative analysis of DNA methylation in 98 GC cases and 64 controls nested within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort and in cancer tissue and non-tumorigenic adjacent tissue of an independent series of GC samples. A panel of 10 cancer-associated genes (CHRNA3, DOK1, MGMT, RASSF1A, p14ARF, CDH1, MLH1, ALDH2, GNMT and MTHFR) and LINE-1 repetitive elements were included in the analysis and their association with clinicopathological characteristics (sex, age at diagnosis, anatomical sub-site, histological sub-type) was examined. Three out of the 10 genes analyzed exhibited a marked hypermethylation, whereas two genes (ALDH2 and MTHFR) showed significant hypomethylation, in gastric tumors. Among differentially methylated genes, we identified new genes (CHRNA3 and DOK1) as targets of aberrant hypermethylation in GC, suggesting that epigenetic deregulation of these genes and their corresponding cellular pathways may promote the development and progression of GC. We also found that global demethylation of tumor cell genomes occurs in GC, consistent with the notion that abnormal hypermethylation of specific genes occurs concomitantly with genome-wide hypomethylation. Age and gender had no significant influence on methylation states, but an association was observed between LINE-1 and MLH1 methylation levels with histological sub-type and anatomical sub-site. This study identifies aberrant methylation patters in specific genes in GC thus providing information that could be exploited as novel biomarkers in clinics and molecular epidemiology of GC.